Click chemistry for improvement in selectivity of quinazoline-based kinase inhibitors for mutant epidermal growth factor receptors. Issue 3 (1st February 2019) - Song, Jiho; Jang, Soyeon; Lee, Jung Wuk; Jung, Danbee; Lee, Seul; Min, Kyung Hoon
Graphical abstract: Abstract: Discovery of mutant-selective kinase inhibitors is one of the challenges in medicinal chemistry and is a main issue for epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors. We tried to improve the selectivity of pan-HER inhibitors for mutant EGFRs. Utilizing click chemistry, triazole-tethered quinazoline derivatives were synthesized, based on a quinazoline scaffold showing pan-HER inhibition. The representative compound 5j exhibited 17- and 52-fold improved selectivity for EGFR L858R/T790M over wild-type EGFR and HER2, respectively, and demonstrated 6.7-fold more potent antiproliferative activity against PC9 cells harboring EGFR-activating mutation than gefitinib. Although the described quinazolines did not surpass pyrimidines as 3rd generation EGFR inhibitors in terms of selectivity for mutant EGFRs, our approach might provide information that would help in the identification of mutant-selective compounds among pan-HER inhibitors using the quinazoline scaffold.